Why Regulation Is Needed in Emerging Markets in the Tourism Sector. - María Martín‐Martín, Jose; Ostos‐Rey, María S.; Salinas‐Fernández, Jose A. (American Journal of Economics & Sociology, 2019)
The neoclassical ideal has defended the idea that markets, in a context of limited regulation, reach an optimal equilibrium automatically. We analyze this assertion in an applied manner with a case study of the emerging online market of intermediation of tourist apartments. The lack of regulation in this market causes many social and economic impacts on local communities, which can jeopardize the survival of the activity. We conclude that an analysis of markets that considers only prices results in a limited view. All externalities and their effects on the population must be taken into account, as well as the interests of the individuals involved, apart from profit‐making.